Perceived outcomes of a biofeedback and neurofeedback training intervention for optimal performance: Learning to enhance self-awareness and self-regulation with olympic athletes - Dupee, M.; Forneris, T.; Werthner, P. (The Sport Psychologist, 2016)
The purpose of this study was to explore the perceived outcomes of a biofeedback and neurofeedback training intervention with high performance athletes. Five Olympic level athletes preparing for world championships and the 2012 Olympic Games took part in a 20 session intervention over the period of one year. At the completion of the intervention, a semistructured interview was conducted with each athlete. The athletes indicated that they became more self-aware, were better able to self-regulate both their physiological and psychological states, developed a greater sense of personal control, and a greater understanding of skills inherent in the field of sport psychology. Three of the athletes made the Canadian Olympic team for the 2012 Olympic Games and two of those athletes won bronze medals. The present study suggests that biofeedback and neurofeedback training may be useful in enabling athletes to perform optimally, in both training and competition, on a consistent basis.